Kombinasi Voice Note dan Mind Mapping dalam Pembelajaran Bahasa Indonesia secara Daring Masa Pandemi Covid-19 - Rina Susi Cahyawati (Jurnal Nomosleca, 2021)
Online   learning   is   one   of   the   alternative solutions set by the government in an effort to carry out an educational climate during the Covid-19 pandemic. Online learning patterns at least require teachers to try to find ways to make distance learning fun and can meet the needs of students for scientific material. The combination of voice notes and mind mapping is an alternative that can be used as a means and media for online learning. The assumption is that most of the participants currently have a WhatsApp application so that it will not make it difficult for them with regards to devices or quotas. Meanwhile, for making mind mapping students can make their versions according to their respective versions so that they will get the sensation of learning while playing. Therefore, the problems of this article are Indonesian language learning technical with a combination of voice notes and mind mapping; and strengths and weaknesses of the implementation of learning Indonesian with a combination of voice notes and mind mapping. The research method used is descriptive qualitative with content analysis. The result of the research is that a combination of voice notes and mind mapping can be used for learning Indonesian online by following the proper technical implementation. The combination of the two has a positive and negative impact on learning. Keywords: Voice Note, Mind Mapping, Indonesian Language Learning